2020
DOI: 10.1002/pon.5371
|View full text |Cite
|
Sign up to set email alerts
|

Cancer worry and empathy moderate the effect of a survivorship‐focused intervention on quality of life

Abstract: Objective This study examined the impact of a survivorship planning consultation (SPC) for patients with Hodgkin's lymphoma and diffuses large B‐cell lymphoma on quality of life (QOL). We specifically assessed two potential moderators, cancer worry and perceived empathy, of the intervention effects on QOL. Methods This cluster randomized, four‐site trial examined the efficacy of a SPC; physicians received communication skills training and applied these skills in a survivorship‐focused office visit using a care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(64 reference statements)
0
9
1
Order By: Relevance
“…Table 1 displays the nine studies with CARE Measure data stratified by SES [44][45][46][47][48][49][50][51][52]. Table 2 displays the 14 studies with CARE Measure data stratified by race/ethnicity [47,51,[53][54][55][56][57][58][59][60][61][62][63][64]. Two studies had CARE Measure data stratified by both SES and race/ethnicity and thus appear in both tables [47,51].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 displays the nine studies with CARE Measure data stratified by SES [44][45][46][47][48][49][50][51][52]. Table 2 displays the 14 studies with CARE Measure data stratified by race/ethnicity [47,51,[53][54][55][56][57][58][59][60][61][62][63][64]. Two studies had CARE Measure data stratified by both SES and race/ethnicity and thus appear in both tables [47,51].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 displays the 14 studies with CARE Measure data stratified by race/ethnicity. 40,44,[49][50][51][52][53][54][55][56][57][58][59][60] Most of the studies were from the United States and the practice settings were diverse, including multidisciplinary practice, orthopedic surgery, emergency medicine, and primary care, among others. Only two studies had CARE Measure data stratified by both SES and race/ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…Congruently, a study in medical oncology found that some cancer patients felt reluctant to communicate with their doctors via a video platform due to feelings of self‐consciousness, and the absence of a physical examination 24,25 . As the perceived empathy of the provider and the patient's anxiety about their cancer can significantly impact the quality of life and oncologic outcome, the lack of rapport could prove to be a great barrier for telemedicine in surgical oncology 26 . Conversely, the burden of expensive oncologic treatments can be mitigated by telemedicine which saves patients on travel expenses, time lost from work, and other related costs 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…24,25 As the perceived empathy of the provider and the patient's anxiety about their cancer can significantly impact the quality of life and oncologic outcome, the lack of rapport could prove to be a great barrier for telemedicine in surgical oncology. 26 Conversely, the burden of expensive oncologic treatments can be mitigated by telemedicine which saves patients on travel expenses, time lost from work, and other related costs. 27,28 The members of SSO noted that there are technological and regulatory obstacles to telemedicine.…”
Section: T a B L E 3 Changes In Practicementioning
confidence: 99%